2020
DOI: 10.3389/fnins.2020.00836
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Sensory Acuity as a Marker of Balance Dysfunction After a Traumatic Brain Injury: A Psychophysical Approach

Abstract: There is limited research on sensory acuity i.e., ability to perceive external perturbations via body-sway during standing in individuals with a traumatic brain injury (TBI). It is unclear whether sensory acuity diminishes after a TBI and if it is a contributing factor to balance dysfunction. The objective of this investigation is to first objectively quantify the sensory acuity in terms of perturbation perception threshold (PPT) and determine if it is related to functional outcomes of static and dynamic balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…BBS has been shown to more strongly correlate with functional measures of balance such as timed up-and-go (TUG) than laboratory measures of body sway during quiet standing or in response to perturbation [60], which is consistent with our findings from our group in the same population [61]. The authors suggested that BBS includes several tasks that may capture several and different functional measures of balance impairment, compared to the more controlled environment of laboratory measures.…”
Section: Effect Of Tbi On Balancesupporting
confidence: 88%
“…BBS has been shown to more strongly correlate with functional measures of balance such as timed up-and-go (TUG) than laboratory measures of body sway during quiet standing or in response to perturbation [60], which is consistent with our findings from our group in the same population [61]. The authors suggested that BBS includes several tasks that may capture several and different functional measures of balance impairment, compared to the more controlled environment of laboratory measures.…”
Section: Effect Of Tbi On Balancesupporting
confidence: 88%
“…Despite a moderate relationship between COP and BBS ( r = −.52, p = .03) in our sample, the two measures may reflect different aspects of balance control. Berg et al found that BBS was more strongly correlated with functional measures of balance such as timed up‐and‐go than laboratory measures of body sway during quiet standing or in response to perturbation (Berg et al, 1992, b), which is consistent with our findings from our group in the same population (Pilkar et al, 2020). The authors suggested that BBS includes various tasks that may capture several and different functional measures of balance impairment, compared to the more controlled environment of laboratory measures (Berg et al, 1992, b).…”
Section: Discussionsupporting
confidence: 91%
“…The number of people with post-concussion syndrome is unclear, with prior studies reporting numbers ranging from 15 to 82% (3,9,15,17). Oculomotor (18), vestibular (19,20), and visualvestibular processing deficits (21)(22)(23) have been reported in the chronic stage of mTBI. These deficits may arise from injury to the peripheral vestibular structures (11,24,25) or due to traumatic central axonal injury (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%